A Bibliometric Study on the Impact of Social Media Use on Mental Health in a Socio-Cultural Context - Judijanto, Loso; Setiawati, Rahmi; Bunyamin, Ilham Akbar (West Science Social and Humanities Studies, 2024)
The growing prevalence of social media has sparked significant academic interest in understanding its impact on mental health. This bibliometric study explores the relationship between social media use and mental health within various socio-cultural contexts, highlighting prevailing themes, trends, and gaps in the literature. Using data from major academic databases, the study identified key research areas, including the association between social media and mental health issues such as depression, anxiety, and addiction, as well as the role of interventions in mitigating these impacts. The findings reveal a strong focus on the negative effects of social media, particularly among adolescents and university students, and emphasize the importance of cultural factors in shaping these outcomes. While interventions and policy recommendations are increasingly being explored, gaps remain in understanding long-term effects, culturally diverse contexts, and potential positive outcomes of social media use. This study underscores the need for continued, multidisciplinary research to inform culturally sensitive practices and policies that address the complexities of social media's impact on mental health.